Escribas semiletrados o iniciadores del castellano bilingüe andino: el caso del copista de Cristóbal de Molina - Cerrón-Palomino, Rodolfo (2016)
This paper seeks to show that a close reading of the only copy of the manuscript Account of the Fables and Rites of the Incas (Ritos y fábulas de los incas) by Cristóbal de Molina makes it evident that Molina’s copyst used a semiliterate Spanish—we are thus dealing with an adulterated copy of the original manuscript. In order to support this hypothesis, four issues are discussed: the constant gaps in the process of copying, the blunders in Spanish literacy, the difficulties in Quechua literacy and the evidence showing the interlect (“castellano motoso”) of the copyist.